How Schools Can Impact Student Retention Among First Nations Students Leading to Higher Graduation Rates? ... - Beebe, Clarice (Graduate Studies, 2013)
This study examines how schools can impact student retention among First Nations students and bring about higher graduation rates. The perceptions and perspectives of eight high school students were examined to discover how effective schools were in helping them succeed academically. First Nations student graduation rates are statistically low across Canada. In 1996, Statistics Canada revealed that 60 percent of First Nations on-reserve residents aged 20-24 had not completed high school or obtained an alternative diploma or certificate (Mendelson, 2008). The 2006 Census results that were released 10 years later reported no change in the data on high school completion among First Nations youth. The researcher conducted a qualitative study in 2011 in order to acquire the perspectives and perceptions of the participants regarding their high school experiences. The study sought to identify what factors in the school positively influenced them and at the same time what barriers they encountered and how the school ...